A Systematic Review of the Efficacy of Levetiracetam in Neonatal Seizures - McHugh, Daryl C.; Lancaster, Shannon; Manganas, Louis N. (Neuropediatrics, 2018)
Objective Seizures are the most common neurological complication in neonatal intensive care units. Phenobarbital (PB) remains the first-line antiepileptic drug (AED) for neonatal seizures despite known neurotoxicity. Levetiracetam (LEV) is a newer AED not approved for neonates. Retrospective and pilot studies have investigated the use of LEV in neonatal seizures. Our objective was to compare the efficacy of LEV to PB in neonatal seizures based upon published data.Methods We searched PubMed to perform a systematic review. We found no studies of LEV with comparison or control groups; therefore, we utilized data from two randomized controlled trials of PB as our comparison group.Results Five studies of LEV met all inclusion/exclusion criteria. The pooled sample size for LEV was 102 (48 received primary LEV, 54 received secondary LEV). The pooled sample size for primary PB was 52. Complete or near-complete seizure cessation was achieved as follows: primary LEV 37/48 (77%), secondary LEV 34/54 (63%), and primary PB 24/52 (46%).Conclusion Our findings suggest that LEV may be at least as or more effective for neonatal seizures as PB. Our review, though limited, is the first to examine LEV efficacy compared with PB in neonates.
Keywords: neonatal seizure; levetiracetam; systematic review